2003
DOI: 10.1016/s0014-5793(03)00981-5
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the efficiency of the electron donation to tyrosine Z of photosystem II in an SQDG‐deficient mutant of Chlamydomonas

Abstract: Photosystem (PS) II activity of a sulfoquinovosyl diacylglycerol (SQDG)-de¢cient mutant (hf-2) of Chlamydomonas was partially decreased compared with that of wild-type. The susceptibility to 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) was also modi¢ed in the mutant. Photometric measurements in the isolated thylakoid membranes of hf-2 revealed that the lowered activity in the mutant was derived from a decrease in the e⁄ciency of the electron donation from water to tyrosine Z, not from the e⁄ciency of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 13 publications
3
34
0
Order By: Relevance
“…Additionally, SQDG has been identified in PSII of Thermosynechococcus elongatus and cytochrome b6f of C. reinhardtii, with its headgroup embedded in the photosynthetic complexes and acyl chain located in the cytoplasm side of the thylakoid membranes (Stroebel et al, 2003;Loll et al, 2005Loll et al, , 2007. Recently, Chlamydomonas mutants deficient in SQDG biosynthesis have been obtained and characterization of the mutant suggested that SQDG plays a structural role for the Q B binding site of PSII, while maintaining a correct conformation at the PS II donor side (Minoda et al, 2003;Riekhof et al, 2003).…”
Section: Remodeling Of the Membrane Glycerolipids In Response To Chanmentioning
confidence: 99%
“…Additionally, SQDG has been identified in PSII of Thermosynechococcus elongatus and cytochrome b6f of C. reinhardtii, with its headgroup embedded in the photosynthetic complexes and acyl chain located in the cytoplasm side of the thylakoid membranes (Stroebel et al, 2003;Loll et al, 2005Loll et al, , 2007. Recently, Chlamydomonas mutants deficient in SQDG biosynthesis have been obtained and characterization of the mutant suggested that SQDG plays a structural role for the Q B binding site of PSII, while maintaining a correct conformation at the PS II donor side (Minoda et al, 2003;Riekhof et al, 2003).…”
Section: Remodeling Of the Membrane Glycerolipids In Response To Chanmentioning
confidence: 99%
“…However, SQD1 activity in SIR Ri plants was apparently insufficient to protect chloroplasts from sulfite. The increased SQDG level in the upper leaves of SIR Ri plants might be also related to additional stabilization of PSII (Minoda et al, 2002(Minoda et al, , 2003 required during enhanced sulfite production.…”
Section: Sir Activity and Sulfite Homeostasis Impacts On Leaf Senescencementioning
confidence: 99%
“…By contrast, in the mutants of C. reinhardtii and Synechocystis sp. PCC6803, PSII activity decreased, and the functional site of PSII damaged in the C. reinhardtii mutant was specified as the electron transfer site from water to Tyr Z in the donor site of PSII (Minoda et al, 2003).…”
mentioning
confidence: 99%